The functions of pauses in penginyongan daily conversation - Chusni Hadiati (University of Muhammadiyah Purwokerto, 2021)
The role of language in daily communication is undoubtedly important because language as a means of communication convey message from speaker to hearer. In the process of transferring message, particularly in oral communication, speaker and hearer may undergo some hesitation and silence cannot be avoided. Silence becomes one specific feature in oral communication. Pause and other phenomenon of spontaneous speech are commonly connected to changes in speakers’ responsiveness in a stable interpersonal situation. Daily conversation is a social praxis that encompasses human life and it is usually conducted in local or indegenous language. Pauses are widely found in this type of exchange and thus the importance of pause in oral talk is worth-analyzing. This paper tries to find out the functions of pauses in Penginyongan daily conversation. Penginyongan is a variant of Javanese language spoken along Serayu River. This research was conducted by using empirical data which were collected by using recording and in-depth interview. Participants of the research were native speaker without considering their sexes. Pauses in Penginyongan daily conversation are used for keeping a secret, refusal, acceptance, end a conversation, and changing topic. A further research needs to develop to gain the insight of pause phenomenon in Penginyongan related to participants’ sexes.